THE EFFECT OF CONSUMER BEHAVIOR ON THE PURCHASE OF OIL FUEL USING MYPERTAMINA APPLICATION AT PUBLIC FUEL FILLING STATIONS IN THE CITY OF SURABAYA (CASE STUDY ON PERTALITE AND PERTAMAX FUEL) - Basyiruddin; Wijayanti, Desie (Sekolah tinggi ilmu ekonomi pemuda, 2022)
The aim of this study was to determine the effect of consumer behavior on the use of the MyPertamina application in purchasing Pertalite and Pertamax fuel oil at Public Fuel Filling Stations (SPBU) in Surabaya. The data studied is the behavior of gas station consumers who use the MyPertamina application when purchasing fuel. Consumers have different behaviors for each individual in making purchasing decisions. This is a demand for business actors to continue to innovate in the all-electronic business world, especially in the field of payments which has become the main trend today. The object of this research is consumers who purchase fuel with the payment method using the MyPertamina application at gas stations in Surabaya. This research method uses a quantitative descriptive approach. The results of this study indicate that consumer behavior has a significant influence on fuel purchases using the MyPertamina application at gas stations in Surabaya.